The Effect of Pregnant Women's Knowledge on Antenatal Care Visit Compliance: a Behavioral Analysis with the Health Belief Model - Renta Sihombing; Nova SN Siregar; Helprida Sihite; Debora Simamora (Jurnal EduHealth, 2025)
Adherence to antenatal care (ANC) visits is a crucial indicator of efforts to reduce maternal and neonatal mortality. Various studies have examined demographic factors, but health behavior analyses using the Health Belief Model (HBM) in the context of ANC attendance in primary healthcare is still limited. To analyze the impact of the HBM dimensions (perceived vulnerability, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy) and knowledge of pregnant women on ANC visits using multivariate logistic regression. This is a quantitative analytical study with a cross-sectional design involving 240 pregnant women. The instruments used were the HBM and knowledge questionnaires. Variables that significantly influenced ANC adherence were knowledge (OR = 2.84; 95% CI: 1.62–4.97; p < 0.001), perceived benefits (OR = 3.11; p = 0.002), and self-efficacy (OR = 2.53; p = 0.007). The logistic regression model showed a good fit (Hosmer-Lemeshow p = 0.34). Knowledge level and components of the Health Belief Model (HBM) significantly contributed to ANC adherence. Health education and communication interventions grounded in the Health Belief Model (HBM) are strongly recommended.